The copper-alloy pin (Scottish Historical and Archaeological Internet Reports, 2012)
A copper-alloy pin with curved neck has no immediate Scottish parallels. It can, however, be compared to a small number of pins from elsewhere in Britain and Ireland belonging to a wider family of so-called swan's neck and ring-headed pins of mainly early Iron Age date.